Green synthesis of low-cost graphene oxide-nano zerovalent iron composite from solid waste for photocatalytic removal of antibiotics - Aditya Kumar Jha; Sukalyan Chakraborty; Jayanta Kumar Biswas (iScience)
Summary: This study develops a graphene oxide-nano zerovalent iron (GO-nZVI) composite for the efficient removal of tetracycline and ciprofloxacin from water. The composite was synthesized using sugarcane bagasse as the matrix for graphene oxide (GO) and Sal leaf extract to reduce iron into nano zerovalent iron (nZVI). Microscopic analysis confirmed multiple GO layers with nZVI particles on their surface, while XRD and Raman spectroscopy verified the crystalline nature of the composite. Photocatalytic degradation achieved removal efficiencies of 91% for tetracycline and 92% for ciprofloxacin. The microbial assays showed that the degraded antibiotics were non-toxic, ensuring their safe disposal. Treatment costs were estimated at 53 USD for tetracycline and 68 USD for ciprofloxacin per 10,000 L of contaminated water. This approach provides a sustainable solution by employing agricultural waste in environmental remediation, supporting a circular economy model for tackling antibiotic contamination in water.